2019
DOI: 10.3390/f10070557
|View full text |Cite
|
Sign up to set email alerts
|

Leaf and Soil δ15N Patterns Along Elevational Gradients at Both Treelines and Shrublines in Three Different Climate Zones

Abstract: The natural abundance of stable nitrogen (N) isotope (δ15N) in plants and soils can reflect N cycling processes in ecosystems. However, we still do not fully understand patterns of plant and soil δ15N at alpine treelines and shrublines in different climate zones. We measured δ15N and N concentration in leaves of trees and shrubs and also in soils along elevational gradients from lower altitudes to the upper limits of treelines and shrublines in subtropical, dry- and wet-temperate regions in China. The patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 48 publications
1
9
1
Order By: Relevance
“…Their results showed that mature trees at these levels did not differ substantially in their ecophysiological performance due to microclimatic amelioration at microsites above the treeline. Leaf and soil δ 15 N patterns were studied along elevational gradients in tree-and shrublines in three different climatic zones in Wolong Nature Reserve in Southwest China by Wang et al [21], who reported that δ 15 N leaf and δ 15 N soil values were higher in subtropical forests compared to dry and wet-temperate forests.…”
mentioning
confidence: 99%
“…Their results showed that mature trees at these levels did not differ substantially in their ecophysiological performance due to microclimatic amelioration at microsites above the treeline. Leaf and soil δ 15 N patterns were studied along elevational gradients in tree-and shrublines in three different climatic zones in Wolong Nature Reserve in Southwest China by Wang et al [21], who reported that δ 15 N leaf and δ 15 N soil values were higher in subtropical forests compared to dry and wet-temperate forests.…”
mentioning
confidence: 99%
“…Soil δ 15 N values tend to increase with increasing temperature and decrease with increasing precipitation across spatial gradients (Craine et al ., 2015b). However, global relationships between soil δ 15 N values and climate are largely indirect and can be influenced a number of other variables, including soil depth (Natelhoffer & Fry, 1988; Jobbágy & Jackson, 2001; Hobbie & Ouimette, 2009), soil age (Brenner et al ., 2001), elevation (Wang et al ., 2019), dominant plant species (Templer et al ., 2007), and clay and carbon concentrations (Craine et al ., 2015b). Soil pH is an important underlying driver of broad spatial patterns in soil δ 15 N values, as arid land soils tend to be alkaline and therefore susceptible to gaseous losses of NH 3 (McCalley & Sparks, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The various studies suggested that the responses of soil and plant δ 15 N to warming were very complex and not well understood. In addition to climate factor, soil and plant δ 15 N are affected by a variety of other environmental factors, such as vegetation type, topography, soil properties and management practices (Gurmesa et al, 2017;Wang et al, 2019). However, we know little about the influences of environmental factors on the warming effect on ecosystem N cycling, in terms of soil and plant δ 15 N.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature has been demonstrated to be a key factor to regulate the soil δ 15 N by influencing the processes of N mineralization, nitrification and denitrification. The higher temperature can strengthen the activity of soil microbes and thereafter increase the N uptake for plants and soil N loss from ammonia volatilization and gas N emissions, and thereby more 15 N-enriched retains in soils(Wang et al, 2019). High d values of soil δ 15 N corresponded to MAT of about 20 o C, which was the most suitable temperature for nitrification and denitrification.…”
mentioning
confidence: 96%